PROJECT-BASED 21S- CENTURY THEMATIC LEARNING MEDIA DEVELOPMENT USING SAC FOR ELEMENTARY SCHOOL STUDENTS - Eva Aina Husna (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2022)
This study aims to develop project-based thematic learning media using SAC to improve 21st-century skills for fifth-grade elementary school students and test the learning media's feasibility, practicality, and attractiveness. The research method used is development research or called RD. The research model used is the Borg and Gall development model. The implementation of the development steps does adjust to the needs of the researcher. Given the limited time and funds owned by the researchers, simplified these steps into four steps: data collection, planning, product development, validation, and trials. The questionnaire consisted of media experts, material experts, learning experts, practitioners (teachers), and student responses. The research used quantitative and qualitative descriptive techniques. The results from the media expert validation got a score of 68.89 or categorized as "Eligible." The material expert's assessment results got a score of 93.84 with the "Very Eligible" category. The score of the learning expert assessment is 83.63 categorized as "Very Eligible." obtained the feasibility of the media from the teacher's evaluation with a score of 82.85 categorized as "Very Eligible." The student questionnaire assessment got a score of 83.92 or "Very Eligible." All expert validations, teacher assessments, and student responses obtained an average score of 82.96 which means the project-based thematic learning media of SAC is "Very Eligible." So it can conclude that this learning media is appropriate for improving elementary school students' skills in the 21st century.